(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article investigates the influence of the volume and intensity of training loads on body weight loss indicators in taekwondo athletes aged 18–21. The aim of the study is to determine the influence of the volume and intensity of training loads on the amount of body weight loss in taekwondo athletes who use the Pacer fitness application for smartphones. The study was conducted by the public organization “Taekwondo Federation (WTF) of Ukraine”. It was attended by 36 elite athletes of Ukraine, specializing in taekwondo WTF, aged 18–21. During a month of training using the Pacer mobile application, athletes demonstrated an average body weight loss of 1.31±0.09 kg per session. The average volume of their training loads was 5825.44±455.61 EC, and the duration was 128.75±2.41 min. The study found strong correlations between the decrease in body weight of athletes from the volume of training loads r=0.92, at p<0.001, and the rate of body weight loss from the intensity of training loads r=0.896, at p<0.001. Regression models were developed for the dependence of the rate of decrease in body weight of taekwondo athletes from the intensity of training loads with a coefficient of determination R2=0.8026 and the dependence of the decrease in body weight of athletes from the volume of training loads – R2=0.8484. Taekwondo WTF, like most martial arts, is structured by weight categories, and among athletes and coaches it is common to use weight adjustment strategies to participate in competitions in lower weight categories. The strategy for reducing body weight of athletes should be based on aspects of avoiding the risks of harmful effects on the body of taekwondo athletes. The results of a study of the impact of the volume and intensity of training loads on the amount of weight loss of an athlete using the Pacer mobile application allow you to choose the optimal volume and intensity of training loads, which will contribute to effective management of the weight loss process without harm to health.